Interview with Luigi Abbate - Abbate, Luigi; Campolina, Eduardo; Maia, Igor Leão (Revista Vórtex, 2020)
In this article we interviewed the Italian composer Luigi Abbate. In our conversation we focused on music composition teaching, its developments and challenges. We started from the historical view of Professor Abbate, in order to carry out a brief comparative analysis of Italian and Brazilian music education. During the conversation, we passed through subjects such as the curriculum of composition courses, the use of the classical repertoire in class and the didactics of teaching music composition.